2017
DOI: 10.1160/th16-11-0856
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant GPVI-Fc added to single or dual antiplatelet therapy in vitro prevents plaque-induced platelet thrombus formation

Abstract: The efficiency of current dual antiplatelet therapy might be further improved by its combination with a glycoprotein (GP) VI-targeting strategy without increasing bleeding. GPVI-Fc, a recombinant dimeric fusion protein binding to plaque collagen and concealing binding sites for platelet GPVI, acts as a lesion-focused antiplatelet drug, and does not increase bleeding in vivo. We investigated, whether GPVI-Fc added in vitro on top of acetylsalicylic acid (ASA), the P2Y antagonist ticagrelor, and the fibrinogen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Under flow, platelet inhibition by GPVI‐CD39 was more pronounced than adding a full ex vivo dose of the ADP receptor inhibitor ticagrelor to GPVI‐Fc: Comparing the results of the current study with those of our previous results, 150 nmol/L GPVI‐CD39 was equally effective in inhibiting plaque‐induced platelet aggregation (81% inhibition) as the combination of 150 nmol/L GPVI‐Fc with 3.82 μmol/L of the ADP receptor antagonist ticagrelor (79% inhibition). This comparison underscores the relative potency of the GPVI‐CD39 fusion protein compared with existing antiplatelet drugs.…”
Section: Discussionsupporting
confidence: 63%
“…Under flow, platelet inhibition by GPVI‐CD39 was more pronounced than adding a full ex vivo dose of the ADP receptor inhibitor ticagrelor to GPVI‐Fc: Comparing the results of the current study with those of our previous results, 150 nmol/L GPVI‐CD39 was equally effective in inhibiting plaque‐induced platelet aggregation (81% inhibition) as the combination of 150 nmol/L GPVI‐Fc with 3.82 μmol/L of the ADP receptor antagonist ticagrelor (79% inhibition). This comparison underscores the relative potency of the GPVI‐CD39 fusion protein compared with existing antiplatelet drugs.…”
Section: Discussionsupporting
confidence: 63%
“…46 GPVI-Fc did not increase bleeding in vitro, nor in mice and human volunteers in vivo even given on top of standard anti-platelet drugs (aspirin, P2Y12 receptor antagonists). 11,40,47 However, GPVI-Fc was less effective than Btk inhibitors in inhibiting plaque-induced platelet aggregation under static conditions and at low arterial shear flow in vitro, [10][11][12]48 and in contrast to Btk inhibitors has to be given intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Btk is also expressed in platelets and involved in signal transduction of the collagen receptor glycoprotein (GP) VI. 5,6 Direct GPVI antagonists (antibodies, recombinant GPVI-Fc) preferentially inhibit platelet activation by collagenous material exposed after plaque rupture and erosion, [7][8][9][10][11] and we recently demonstrated that Btk inhibitors also selectively prevent atherosclerotic plaque-triggered platelet thrombus formation. 12 Collagen-induced platelet adhesion and aggregation under arterial flow requiring integrin α2β1 not being affected by Btk inhibitors was not inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal structure of plaque collagens might explain, why plaques activate mainly GPVI and barely the integrin α2β1 on platelets: recombinant GPVI-Fc (Revacept) which binds to collagen, and anti-GPVI but not anti-integrin α2β1 antibodies inhibit plaque-induced platelet thrombus formation. [4][5][6]21,22 In flow chamber experiments using hirudin-or heparin-anticoagulated blood, anti-integrin α2β1 antibodies did not impair platelet thrombus formation on human atherosclerotic plaque homogenate from arterially flowing blood. 4,6 Similar results were observed using blood from integrin α2-deficient mice.…”
Section: Introductionmentioning
confidence: 95%